User acceptance of 2D embryology animation: early embryogenesis made easy - Yin, Chin Hui; Jaysri, Faris Hazreen; Wan Mohamed Zuri, Wan Nur Syaziyah; Nasharuddin, Nurul Amelina; Mohd Nor, Nurul Huda; Sa'at, Azmah; Hod, Rafidah; Mohd Nazan, Ahmad Iqmer Nashriq; Mohamad Asri, Siti Fadziyah; Abas, Razif (Universiti Putra Malaysia Press, 2024)
Introduction: Embryology, the study of embryo and foetal development, is essential in medical education but often lacks consistent instructional resources. Embryology education in medical institutions primarily relies on traditional lectures, presenting inconsistencies in content depth and duration. To address these limitations, multimedia integration, particularly 2D animations, has been introduced to enhance understanding and retention of embryological concepts. This study aimed to assess medical students’ perceptions of a 2D embryology animation depicting early embryogenesis through a user acceptance test. Materials and methods: A group of 20 Year 2 medical students underwent this assessment, evaluating usability, learnability, memorability, understanding, and motivation via a Likertscale questionnaire. A descriptive analysis of mean and standard deviation was conducted using SPSS software. Results: Results revealed positive perceptions across genders and ethnicities in usability, learnability, memorability, understanding, and motivation, emphasizing the animation’s effectiveness in engaging learners. However, disparities emerged among demographic groups, suggesting a need for tailored approaches to optimise digital learning experiences. Limitations included the small sample size and focus on a specific embryonic stage, urging further studies with broader participant pools and diverse educational stages for improved generalizability. Conclusion: Our findings underscore the significance of multimedia in medical education and advocate for further refinement of such approaches to foster inclusive and effective learning environments.